The Benefit of Films in Nursing Education: A Rapid Review - Adiningsih, Berthy Sri Utami; Saifudin, I Made Moh. Yanuar; Fradianto, Ikbal (GLOBAL HEALTH SCIENCE GROUP, 2024)
Traditional teaching methods in health education often emphasize cognitive aspects. Cinemeducation is non-traditional learning method that using film that has been used recently in medical education to enhance psychosocial skills, but less explored in nursing education. This study aims to evaluate the benefits of using films as a learning tool, especially for nursing education. A rapid review methodology was employed following the PRISMA guidelines. The review covered papers published between 2018 and 2024, focusing on healthcare students particularly in nursing and medicine. Consensus App and ResearchGate databases were searched with terms “